Association between Occupational Stress and Psychopathological Symptoms Among Nurses in Cardiovascular Hospital During COVID-19 Pandemic - Ayu Munawaroh; Herqutanto; Khamelia Malik; Ambar W. Roestam; Astrid B. Sulistomo (ILUNI MKK FKUI and PRODI MKK FKUI, 2022)
Introduction: Occupational stress is known to be one of the factors that are often found in nursing professionals. Occupational stress can affect a person both physically and mentally. Moreover, the COVID-19 pandemic has brought additional workload for healthcare professionals, including nurses. This study aimed to analyze the association between occupational stress and psychopathological symptoms among nurses in Cardiovascular Hospital during the Covid-19 pandemic. Methods: This cross-sectional study involved 108 nurses in Cardiovascular Hospital X. Samples were taken by simple random sampling based on inclusion and exclusion criteria. Occupational stress was assessed by Expanded Nursing Stress Scale (ENSS) and psychopathological symptoms were assessed by Symptom Checklist 90 (SCL-90). Results: The mean ENSS total score was 88,17 ± 32,24 (maximum score of ENSS was 228). 19,4% of nurses had psychopathological symptoms. Somatization, obsessive-compulsive, and psychoticism had higher t-score values than other SCL-90 subscales. There was a strongly significant association between occupational stress and psychopathological symptoms (p<0,001). Conclusion: Its highly recommend early diagnosis and prompt treatment for psychopathological symptoms among nurses. Monitor and evaluation of occupational stress and psychopathology in nurses are recommended as periodic medical check-up program in hospital.